A comparative analysis on the dexterity skills of the students of the UPCD - Maronilla, Eileen L.
This study explores the difference in the psychomotor skills among the students of the UPCD. Ninety students were chosen by random sampling design took part in the study. Two sets of tests were administered namely, the perception and control test and the psychomotor ability test. In the two tests, the fourth year students exhibited the best performance followed by the second years and then the third years. There is a moderately positive correlation between the two tests but the psychomotor ability test proved to be better in predicting psychomotor ability.